Analisis Determinan Pertumbuhan Industri Provinsi Sumatera Utara - Tetty Sipahutar; Yeni Rafita Sihombing (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2019)
The influence of industrial development on economic growth in North Sumatra over the past decade has become a recurring problem as economic analysis especially of growing regions. North Sumatra has enjoyed a long period of economic growth however, there is a bad contribution from the industrial sector to the North Sumatra province's GDP regional. There are various studies that have supported that increasing the number of industries is the path to sustainable economic growth. Thus, this study aims to review research conducted in the field of determinants and factors that influence the growth of the number of industries. This review highlights that most studies have been carried out to establish a relationship between the Number of Industries, the Open Unemployment Rate, and the Population Amount, to the Gross Regional Domestic Product. To conclude, the main industry growth factors identified are relevant to increasing economic growth in North Sumatra: status of foreign direct investment, employment of people, government financial support - investment incentives, marketing strategies to attract investors, overall readiness and availability of a number of industries with a focus on effects positive regional development, using regional GDP per capita, specifically to reduce regional unemployment rates.